TALENT MANAGEMENT: EFFECTS ON ORGANIZATIONAL PERFORMANCE IN CREATING COMPETITIVE ADVANTAGE - Abdul Aziz (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
In the midst of competition between companies as it is today, creating a competitive advantage is an absolute must for companies. One way to create excellence is with the presence of human resources who have the ability, knowledge and skills according to the company's needs. HR is the most important capital for the smooth operation of the company. So many companies like today are far paying attention to their human resources. To manage HR in a good direction, talent management is needed in improving and developing HR potentials within the company. The purpose of this study was to examine the effect of talent management and employee engagement on employee performance at CV. Maxmoda Indo Global. The method used in this study is to use the census method with the help of the SPSS program to process the collected data. The partial test results show that talent management has a significant effect on employee performance. From the simultaneous test, it can be seen that employee engagement has a positive and significant effect on employee performance. Talent management and employee engagement together have a positive and significant impact on employee performance.